Mechanical, Rheological, and Bioactivity Properties of Ultra High-Molecular-Weight Polyethylene Bioactive Composites Containing Polyethylene Glycol and Hydroxyapatite - Mazatusziha Ahmad; Mat Uzir Wahit; Mohammed Rafiq Abdul Kadir; Khairul Zaman Mohd Dahlan (The Scientific World Journal)
Ultrahigh-molecular-weight polyethylene/high-density polyethylene (UHMWPE/HDPE) blends prepared using polyethylene glycol PEG as the processing aid and hydroxyapatite (HA) as the reinforcing filler were found to be highly processable using conventional melt blending technique. It was demonstrated that PEG reduced the melt viscosity of UHMWPE/HDPE blend significantly, thus improving the extrudability. The mechanical and bioactive properties were improved with incorporation of HA. Inclusion of HA from 10 to 50 phr resulted in a progressive increase in flexural strength and modulus of the composites. The strength increment is due to the improvement on surface contact between the irregular shape of HA and polymer matrix by formation of mechanical interlock. The HA particles were homogenously distributed even at higher percentage showed improvement in wetting ability between the polymer matrix and HA. The inclusion of HA enhanced the bioactivity properties of the composite by the formation of calcium phosphate (Ca-P) precipitates on the composite surface as proven from SEM and XRD analysis.